Clinical differences between small and large pheochromocytomas and paragangliomas - Zhao, Lin; Li, ZhiMao; Meng, Xu; Fan, Hua; Zhang, ZengLei; Zhang, ZhaoCai; Liu, YeCheng; Zhou, XianLiang; Zhu, HuaDong (Frontiers in Endocrinology, 2023)
Background: Pheochromocytomas and paragangliomas (PPGLs) are neuroendocrine tumors, most of which are characterized by the release of catecholamine, and range in diameters from less than 1 cm to 10 cm or more. However, knowledge of the differences in clinical features between small and large PPGLs is insufficient. Methods: A retrospective analysis of patients with PPGLs treated at our institution between January 2018 and June 2020 was performed. The clinical characteristics of patients were investigated, and comparisons were made between patients with large and small PPGLs. The logistic regression analysis was used to confirm the risk factors, and the receiver operating characteristic curve was used to evaluate the diagnostic performance of the variables. Results: Totally 263 patients were included, including 110 patients in small tumor group and 153 patients in large tumor group. There were more male patients in the large tumor group (p=0.009). More patients had hypertension (p<0.001) and diabetes (p=0.002) in the large tumor group. The 24-h urinary epinephrine (24hU-E) (p < 0.001) and 24-h urinary norepinephrine (24hU-NE) (p=0.002) concentrations were higher in the large tumor group. In terms of tumor location, adrenal-PPGLs were more frequent in the large tumor group (p<0.001). Multivariate logistic regression analysis showed that male sex [odds ratio (OR): 2.871, 95% confidence interval (CI): 1.444–5.711, p=0.003], 24hU-E (OR: 1.025, 95% CI:1.004–1.047, p=0.020), 24hU-NE (OR: 1.002, 95%CI: 1.001–1.004, p=0.045), and adrenal-PPGLs (OR: 2.510, 95% CI:1.256–5.018, p=0.009) were positive risk factors for large tumors. Taking above variables into the same model, the area under the receiver operating characteristic curve of the model for predicting the large tumor was 0.772 (95% CI: 0.706–0.834). After the short-term follow-up, there was no significant difference in tumor recurrence between the two groups (p=0.681). Conclusions: Significant differences in numerous clinical characteristics exist between large and small PPGLs. The male patients were more likely to be with large tumors, and such tumors were more likely to reside on the adrenal glands. Catecholamine measurements also help predict tumor size of PPGLs. Clinical decision-making will benefit from this information.